Annual to decadal temperature adaptation of the soil bacterial community after translocation across an elevation gradient in the Andes. (July 2021) - Nottingham, A.T.; Hicks, L.C.; Meir, P.; Salinas, N.; Zimmermann, M.; Bååth, E.
Abstract: The response of soil microbial activity to climate warming has been predicted to have a large destabilising effect on the carbon cycle. However, the nature of this feedback remains poorly understood, especially in tropical ecosystems and across annual to decadal timescales. We studied the response of bacterial community growth to 2 and 11 years of altered temperature regimes, by translocating soil across an elevation gradient in the tropical Andes. Soil cores were reciprocally translocated among five sites across 3 km in elevation, where mean annual temperature (MAT) ranged from 26.4 to 6.5°C. The bacterial community growth response to temperature was estimated using a temperature Sensitivity Index (SI): the log-ratio of growth determined by leucine incorporation at 35°C: 4°C. Bacterial communities from soil translocated to their original site (controls) had a growth response assumed to be 'adapted' to the original MAT. Translocating soil downslope (warming) resulted in an increased SI relative to their original growth response, and vice versa under cooling, indicating community-level adaptation over the incubation period to the altered MAT. The average level of adaptation (i.e., the extent to which SI converged on the control values) was 77% after 2 years, and was complete after 11 years. The adaptive response was faster when soil was warmed rather than cooled: instances of complete adaptation of SI occurred in soils after 2 years when warmed, but only after 11 years when they were cooled. Taken together, our results show that the majority of the growth adaptation to warming by the bacterial community occurs rapidly, within 2 years, whilst growth adaptation to cooling occurs within a decade. Our analysis demonstrates rapid warm-adaptation of bacterial community growth, with potential consequences for the temperature sensitivity of soil carbon cycling in response to future climate warming. Highlights: Soil bacterial growth is adapted to temperature difference with elevation in the tropics. Growth responded to 2–11 yrs of imposed warming and cooling by ± 4–20 °C. Two years of temperature change resulted in 77% temperature adaptation of growth. Temperature adaptation of bacterial growth was complete ( 100%) after 11 years. Adaptation of bacterial growth was more rapid under warming compared to cooling.